SOME LEGAL ASPECTS OD STOCK RIGHTS. - Briggs, L. L. (The Accounting Review, 1932)
Abstract This article is an attempt to state the fundamental legal principles governing the rights of holders of original shares in a corporation to subscribe when that corporation issues new or unissued stock. The general rule is that when new shares are issued for money each `holder of the original stock is entitled to a prior right to subscribe in the proportion that his shares bear to the total issue before the increase If part of the authorized capital stock of a corporation remains unissued, in the absence of a statute to the contrary, each stock- holder has a right to purchase such proportion of it, when the issuance and sale thereof are directed, as his holdings bear to the stock then outstanding. It has been held that the right to issue the remaining stock is a corporate franchise, held by the corporation in trust for the corporators, and that this right must be used for the benefit of all the shareholders. The same rule applies to the corporation which has issued and sold but part of its authorized stock and later decides to issue the unissued shares.